Peranan Media dalam Pemberitaan Penggalian Arkeologis di Situs Takengon Berdasarkan Teori Agenda Setting - Defri Elias Simatupang (Berkala Arkeologi Sangkhakala, 2009)
AbstractThis article tries to describe the extent to which the public interest against an archaeological excavation that has been covered by mass media. By using the approach of mass communications (agenda setting theory), it is tried to make a model of how to link the interest of various stake holders to the news coverage of archaeological excavation in order to achieve the optimum benefit..